2016
DOI: 10.1002/2015gc006106
|View full text |Cite
|
Sign up to set email alerts
|

Alkenone paleothermometry in the North Atlantic: A review and synthesis of surface sediment data and calibrations

Abstract: Despite a clear correlation of alkenone unsaturation and sea surface temperatures (SST) throughout most parts of the ocean, scatter of the regression for various calibration equations has been shown to increase significantly at low SSTs. In this study, we combine previously published (n 5 101) and new (n 5 51) surface sediment data from the northern North Atlantic to constrain uncertainties of alkenone paleothermometry at low SSTs and to discuss possible sources of the increased scatter in the regression. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 49 publications
1
34
0
1
Order By: Relevance
“…However, the absolute U 37K values at some of these locations are similar to those found in subtropical waters (∼0.5–0.7), indicating either very far field advection or that another process is influencing alkenone unsaturation. Filippova et al () observed that although sea ice intensity is not correlated with U 37K residuals in the high‐latitude North Atlantic, nearly all of the samples with higher U 37K values than expected are from locations with some sea ice cover. Indeed, we find that the most positive residuals in the Norwegian and Labrador Seas generally, although not exclusively, fall within areas with at least 5% annual ice cover (Figure a) and that there is a significant correlation between U 37K residuals and the percentage of annual sea ice cover (Spearman's ρ = 0.52, p < 0.0001).…”
Section: Data Exploration: Residual Trends Seasonality and Nonlineamentioning
confidence: 93%
See 2 more Smart Citations
“…However, the absolute U 37K values at some of these locations are similar to those found in subtropical waters (∼0.5–0.7), indicating either very far field advection or that another process is influencing alkenone unsaturation. Filippova et al () observed that although sea ice intensity is not correlated with U 37K residuals in the high‐latitude North Atlantic, nearly all of the samples with higher U 37K values than expected are from locations with some sea ice cover. Indeed, we find that the most positive residuals in the Norwegian and Labrador Seas generally, although not exclusively, fall within areas with at least 5% annual ice cover (Figure a) and that there is a significant correlation between U 37K residuals and the percentage of annual sea ice cover (Spearman's ρ = 0.52, p < 0.0001).…”
Section: Data Exploration: Residual Trends Seasonality and Nonlineamentioning
confidence: 93%
“…We compiled core‐top U 37K data from previous global calibration efforts (Conte et al, ; Müller et al, ), regional studies of U 37K patterns (Benthien & Müller, ; Cacho, Pelejero et al, ; Chen et al, ; Doose et al, ; dos Santos et al, ; Fallet et al, ; Filippova et al, ; Herbert et al, ; Ho et al, ; Jaeschke et al, ; Kaiser et al, ; Kienast et al, ; Kim et al, ; Leduc et al, ; Lee, Kim et al, ; Leider et al, ; Madureira et al, ; Mohtadi et al, ; Ohkouchi et al, ; Pelejero & Grimalt, ; Prahl et al, , ; Rodrigo‐Gámiz et al, ; Rosell‐Melé et al, , ; Rosell‐Melé, ; Sawada et al, ; Sikes et al, , ; Sonzogni et al, ; Tao et al, ), and Late Quaternary studies where a modern or latest Holocene core top was measured (Arz et al, ; Bard et al, ; Barron et al, ; Barrows et al, ; Becker et al, ; Bendle & Rosell‐Melé, ; Budziak et al, ; Cacho, Grimalt et al, ; Cacho et al, ; Calvo et al, , ; Caniupán et al, ; Chapman et al, ; Dubois et al, ; Emeis et al, , ; Fraser et al, ; Gutiérrez et al, ; Harada et al, ; Herbert et al, ; Horikawa et al, ; Huang et al, ; Ikehara et al, …”
Section: Data Compilation and Analytical Methodsunclassified
See 1 more Smart Citation
“…In the Nordic Seas cool and fresh water masses are closely linked (Bendle et al, 2005;Sikes and Sicre, 2002), which is why a distinct separation of a temperature and salinity response of this proxy may not be possible. We consider increases of %C 37 : 4 to be a supporting indicator for an increased influence of both colder and fresher water masses (Bendle et al, 2005;Filippova et al, 2016), in particular at instances when IRD peaks coincide with C 37 : 4 peaks. An alternative approach exploits the co-variation of SST and salinity in the Nordic Seas, as well as the presence of specific surface water masses (Bendle et al, 2005) which showed that elevated %C 37 : 4 and low SSTs occurred in colder and less saline Arctic waters, and this is the interpretation we apply here.…”
Section: Depthmentioning
confidence: 99%
“…Alkenone paleothermometry is used to generate a high‐resolution record of SST. Alkenone‐based temperature reconstructions in the Nordic seas are sparse and often challenged by temperatures below a correlation limit of −5°C (Bendle et al, ; Conte et al, ; Filippova et al, ; Sicre et al, ). Previous studies have shown that the local signal in SE‐Greenland fjords can be biased by nearby highly alkenone productive waters such as south of Iceland or local upwelling, calling for cautious interpretation of the alkSST reconstruction (Andresen et al, , ).…”
Section: Methodsmentioning
confidence: 99%